Ecological implications of changing hatchery practices for Chinook salmon in the Salish Sea - Benjamin W. Nelson; Andrew O. Shelton; Joseph H. Anderson; Michael J. Ford; Eric J. Ward (Ecosphere, 2019)
Abstract For over a century, hatchery programs have been used to subsidize natural salmon populations in order to increase fisheries opportunities and, more recently, to conserve declining natural populations. While an extensive literature has described the impacts of large‐scale hatchery operations on freshwater ecosystems, less attention has been given to ecosystem interactions within the marine environment. We analyzed records of hatchery‐released Chinook salmon in the Salish Sea to assess temporal and spatial changes in hatchery practices since 1950, with the goal of identifying potential implications for ecosystem dynamics and conservation efforts in the region. Over the past 65 yr, we found significant changes in the size and time at which juvenile salmon are released, resulting in decreased diversity of these traits. Research suggests that predation on juvenile salmon by other fish, avian, and marine mammal species could be size‐dependent, and our results indicate that current hatchery practices are releasing Chinook salmon in the size range preferred by these predators. With current marine survival rates at chronically low levels, and increasing demand for hatchery subsidies, it is important to consider how modifying existing hatchery programs intended to reduce homogenization may promote more natural marine food web dynamics, with potential benefits to both hatchery and natural Chinook populations.